Mechanism of Haemophilus influenzae transfection by single and double prophage deoxyribonucleic acid. - Stuy, J H (1980)
Whole phages HP1 and HP3, vegetative-phage deoxyribonucleic acid (DNA), and single and tandem double prophage DNA were exposed to ultraviolet radiation and then assayed on a wild-type (DNA repair-proficient) Haemophilus influenzae Rd strain and on a repair-deficient uvr-1 strain. Host cell reactivation (DNA repair) was observed for whole-phage and vegetative-phage DNA but not for single and double prophage DNA. Competent (phage-resistant) Haemophilus parainfluenzae cells were normally transfected with H. influenzae-grown phage DNA and with tandem double prophage DNA but not at all with single prophage DNA. CaCl2-treated H. influenzae suspensions could be transfected with vegetative phage DNA and with double prophage DNA but not with single prophage DNA. These observations support the hypothesis that transfection with single prophage DNA occurs through prophage DNA single-strand insertion into the recipient chromosome (at the bacterial att site) followed by DNA replication and then prophage induction.